PRODUCTIVE WAQF FOR THE MODERNIZATION PESANTREN (EDUKASIA, 2019)
The article aims to investigate the role of waqf in the modernization of education in Pesantren, by using a case study of the utilization of productive waqf at Modern Pesantren of Gontor and Pesantren of Tebuireng Jombang. The Method used is qualitative with phenomenological approach and comparative study. The result of the study shows that the pesantren built with Islamic philantrophy in the form of waqf institution is a good model for development of pesantren education in Indonesia’s contemporary era. The development process of waqf pesantren of Gontor Modern Pesantren and Tebuireng Pesantren is carried out with several supporting pillars, including: the pesantren administrators’ dedication of their wealth as waqf, the professional institutionalization of waqf pesantren in the form of the foundation’s legal entity, the productive management of waqf assets, and the productive utilization of waqf for the development of education. Both pesantrens have proven that the foundations’ nazir (administrator of waqf) have succeeded in productively managing the waqf in the pesantren community. This further cement the importance of pesantren as an integral part of the society.